Comparison between Conventional Method and Cradle-to-Cradle Method of Waste Management Method - Noor Yasmin Zainun; Iffah Hafizah Yusri (Journal of Structural Monitoring and Built Environment, 2024)
Concrete is a widely used material in the construction industry. Rice huskash and coal bottom ash are by-product materials chosen to alternate the use of cementand sand in concrete production. Concerns about the long-term performance ofseawater concrete structures incorporated with RHA-CBA have been obstacles to thedeveloping uses of sustainable concrete due to the scarcity of knowledge and test data.Thus, the long-term performance of seawater concrete consisting of RHA as cementreplacement and CBA as sand replacement on compressive strength and carbonationwas evaluated in this study. To accomplish the study's goal, existing specimens aged1 year and 4 months, and 2 years with different mixture series were used. In themixture, seawater was utilized to fully replace freshwater, along with 10% RHA usedto replace cement. Additionally, 10% to 100% CBA replaced the sand with a 10%increment. The specimens consisted of 68 cylindrical concretes in 100  100 mm and100  200 mm exposed to indoor environmental conditions. Compressive strengthand carbonation tests were performed to assess the strength and durability of theconcrete. The results indicate that the concretes' strength grows insignificantly in theatmospheric environment within exposure age. After a prolonged period, thespecimen's strength development reduces as the amount of CBA in the concretemixture increases. Meanwhile, test results revealed that RHA-seawater concretecontaining CBA exhibited minimal carbonation after 2 years of aging. Higherincorporation of CBA in the concrete mixture leads to a greater carbonation rate,reducing the concrete’s alkalinity. The findings of this study contribute to theunderstanding and advancement of long-term performances of sustainable concretematerials for construction practices.